Taxonomy and systematics of the fungus-growing ant associate Escovopsis (Hypocreaceae) - Montoya, Q. V. [UNESP]; Martiarena, M. J.S. [UNESP]; Rodrigues, A. [UNESP] (My University, 2023)
Escovopsis is a symbiont of fungus-growing ant colonies. Unstandardised taxonomy prevented the evaluation of the morphological diversity of Escovopsis for more than a century. The aim of this study is to create a standardised taxonomic framework to assess the morphological and phylogenetic diversity of Escovopsis. Therefore, to set the foundation for Escovopsis taxonomy and allow interspecific comparisons within the genus, we redescribe the ex-type cultures of Escovopsis aspergilloides, E. clavata, E. lentecrescens, E. microspora, E. moelleri, E. multiformis, and E. weberi. Thus, based on the parameters adopted in this study combined with phylogenetic analyses using five molecular markers, we synonymize E. microspora with E. weberi, and introduce 13 new species isolated from attine nests collected in Argentina, Brazil, Costa Rica, Mexico, and Panama: E. breviramosa, E. chlamydosporosa, E. diminuta, E. elongatistipitata, E. gracilis, E. maculosa, E. papillata, E. peniculiformis, E. phialicopiosa, E. pseudocylindrica, E. rectangula, E. rosisimilis, and E. spicaticlavata. Our results revealed a great interspecific morphological diversity throughout Escovopsis. Notwithstanding, colony growth rates at different temperatures, as well as vesicle shape, appear to be the most outstanding features distinguishing species in the genus. This study fills an important gap in the systematics of Escovopsis that will allow future researchers to unravel the genetic and morphological diversity and species diversification of these attine ant symbionts.
Keywords: fungus-growing ants; Hypocreaceae; new taxa; symbiosis; systematics; taxonomic diversity